Multicenter CT image-based anatomic assessment of patients with aortoiliac aneurysm undergoing endovascular repair with iliac branch devices - Panthofer, Annalise; Bresler, Alina-Marilena; Olson, Sydney L.; Kuramochi, Yuki; Eagleton-Pierce, Matthew; Böckler, Dittmar; Schneider, Darren B.; Lyden, Sean P.; Blackwelder, William C.; Meadows, Wendy; Pauli, Tom; DeRoo, Elise; et al. (Annals of vascular surgery, 2024)
Background - The Global Iliac Branch Study (NCT05607277) is an international, multicenter, retrospective cohort study of anatomic predictors of adverse iliac events (AIEs) in aortoiliac aneurysms treated with iliac branch devices (IBDs). - Methods - Patients with pre-IBD and post-IBD computed tomography imaging were included. We measured arterial diameters, stenosis, calcification, bifurcation angles, and tortuosity indices using a standardized, validated protocol. A composite of ipsilateral AIE was defined, a priori, as occlusion, type I or III endoleak, device constriction, or clinical event requiring reintervention. Paired t-test compared tortuosity indices and splay angles pretreatment and post-treatment for all IBDs and by device material (stainless steel and nitinol). Two-sample t-test compared anatomical changes from pretreatment to post-treatment by device material. Logistic regression assessed associations between AIE and anatomic measurements. Analysis was performed by IBD. - Results - We analyzed 297 patients (286 males, 11 females) with 331 IBDs (227 stainless steel, 104 nitinol). Median clinical follow-up was 3.8 years. Iliac anatomy was significantly straightened with all IBD treatment, though stainless steel IBDs had a greater reduction in total iliac artery tortuosity index and aortic splay angle compared to nitinol IBDs (absolute reduction −0.20 [−0.22 to −0.18] vs. −0.09 [−0.12 to −0.06], P < 0.0001 and −19.6° [−22.4° to −16.9°] vs. −11.2° [−15.3° to −7.0°], P = 0.001, respectively). There were 54 AIEs in 44 IBDs in 42 patients (AIE in 13.3% of IBD systems), requiring 35 reinterventions (median time to event 41 days; median time to reintervention 153 days). There were 18 endoleaks, 29 occlusions, and 5 device constrictions. There were no strong associations between anatomic measurements and AIE overall, though internal iliac diameter was inversely associated with AIE in nitinol devices (nAIE, nitinol = 8). - Conclusions - Purpose-built IBDs effectively treat aortoiliac disease, including that with tortuous anatomy, with a high patency rate (91.5%) and low reintervention rate (9.1%) at 4 years. Anatomic predictors of AIE are limited.
Onine veröffentlicht: 14. Juli 2024, Artikelversion: 3. August 2024
Gesehen am 26.05.2025